Acid gelation of heat-treated recombined milk: Fat globule membrane composition and gelation functionality. (February 2022) - Anantawat, Visaka; Loveday, Simon M.; Singh, Harjinder; Anema, Skelte G.
Abstract: Recombined whole milk was prepared by heating skim milk before homogenising with milkfat (HEHO milk) or by homogenising milkfat with unheated skim milk and heating the recombined milk (HOHE milk). Heat treatment caused whey protein denaturation, more at higher temperatures and slightly more in HEHO milk than in HOHE milk. Less protein was adsorbed to the fat globules of the HEHO milk than the HOHE milk; the former had a higher proportion of αS -casein and β-casein and a lower proportion of κ-casein and denatured whey proteins at the interface, indicating a different interaction mechanism. Gelation pH and gelation time were similar for acidified HEHO and HOHE samples and correlated to the denaturation of whey proteins. The final G' and yield stresses were lower for the HEHO than the HOHE milk. The differences in gelation behaviour were related to the compositions and interactions of the proteins adsorbed to the fat globules.